ANALYZING LAND USE PATTERN CHANGES IN MUKIM PENGERANG, JOHOR, MALAYSIA - Noordini binti Che Man; Anis Farhan binti Salihin (Geoplanning: Journal of Geomatics and Planning, 2018)
Urbanization and urban land-use transition have a competitive environment to ensure and provide good facilities for citizen benefit. Thus, quantifying the spatiotemporal pattern of urbanization is important for understanding its ecological impacts and can provide basic information for appropriate decision-making. The growth of urbanization in Mukim Pengerang, Johor, has undergone rapid changes in agriculture, settlements, townships and various activities. The changes of the land uses are due to the rapid economic development, which are the Refinery and Petrochemical Integrated Development (RAPID) project and Pengerang Integrated Petroleum Complex (PIPC). The industrialization projects boost the growth in land property and commercial which progressing in rapid development since the year 2012. Therefore, the main aim of this paper is to quantify the changes in landscape pattern or land use pattern between the year 2008 and 2017 occurred in Mukim Pengerang. In monitoring the spatial pattern changes, and the changes of landscape structure, the metrics landscape were analyzed with determination of the Shanon Diversity Index (SHDI), the number of patches (NP), Edge Density (ED) and Total Edge (TE) in the period of 8 years. The results show that the changes occurred with the three types of land use showed significant changes in the types of land use which are forest, agricultural and built-up area. The result of SHDI analysis shows the increment value between the year 2008 and 2017. This situation illustrates that the higher value of SHDI for an area, resulting in the higher level of land use. This is because the growing pattern of land use is reflected by a large number of patches due to the diversification of land use activities in the area. As a result, from the metrics statistics test verifies there was a significant change in land use that took place within 8 years.